Electrodeposition of Cu-Mn Films as Precursor Alloys for the Synthesis of Nanoporous Cu - Ezer Castillo; Nikolay Dimitrov (Electrochem, 2021)
Cu-Mn alloy films are electrodeposited on Au substrates as precursor alloys for the synthesis of fine-structured nanoporous Cu structures. The alloys are deposited galvanostatically in a solution containing ammonium sulfate, (NH4)2SO4, which serves as a source of the ammine ligand that complexes with Cu, thereby decreasing the inherent standard reduction potential difference between Cu and Mn. The formation of the [Cu(NH3)n]2+ complex was confirmed by UV-Vis spectroscopic and voltammetric studies. Galvanostatic deposition at current densities ranging from 100 to 200 mA⋅cm−2 generally resulted in the formation of type I, crystalline coatings as revealed by scanning electron microscopy. Although the deposition current efficiency is (<30%) generally low, the atomic composition (determined by energy dispersive X-ray spectroscopy) of the deposited alloys range from 70–85 at% Mn, which is controlled by simply adjusting the ratio of the metal ion concentrations in the deposition bath. Anodic stripping characterization revealed a three-stage dissolution of the deposited alloys, which suggests control over the selective removal of Mn. The composition of the alloys obtained in the studies are ideal for electrochemical dealloying to form nanoporous Cu.